INTEGRATION OF GREEN ARCHITECTURE PRINCIPLES INTO MULTIFUNCTIONAL RESIDENTIAL COMPLEXES: SOLVING DESIGN TASKS AND APPLICATION IN THE DESIGN OF PHTHISIOLOGY AND PULMONOLOGY HOSPITALS - Vagifovna, Gabibova Irina; ugli, Mamarasulov Muxammadali Normumin (Research Focus International Scientific Journal, 2026)
In the context of intensive urbanization and climate change, the importance of integrating green architecture principles into multifunctional residential complexes is growing. At the same time, creating a safe and therapeutic environment in specialized medical institutions— phthisiology and pulmonology hospitals—is particularly important, where high levels of infection control, air quality, and the creation of a healing environment for patients with respiratory diseases are key requirements.The aim of the study is to identify the key design challenges and objectives in integrating green architecture principles into multifunctional residential complexes and to develop recommendations for their adaptation for the design of modern phthisiology and pulmonology hospitals. Research methods include a systematic analysis of scientific literature, regulatory documents, and international experience, a comparative method, and a graphical analysis of design solutions. Particular attention is paid to biophilic design techniques, natural ventilation, green facades and roofs, and energy-efficient technologies. The study identified key contradictions and limitations in integrating green solutions into multifunctional complexes and proposed architectural planning, engineering, and landscape design approaches to overcome them. It was demonstrated that many effective green practices proven in residential construction (microclimate improvement, passive ventilation, biophilic elements) can be successfully adapted to the specific needs of healthcare facilities, taking into account infection safety requirements. The findings confirm the high potential for transferring green architectural solutions between residential and healthcare design. The practical significance of this work lies in the development of recommendations that can be used by architects and designers in creating sustainable multifunctional residential complexes and modern specialized hospitals, particularly in the arid climate of Central Asia.